2016
DOI: 10.1016/j.indcrop.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of physical and optical properties of biodegradable edible films based on pea starch and guar gum

Abstract: Optimization of physical and optical properties of biodegradable edible films based on pea starch and guar gum"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(94 citation statements)
references
References 54 publications
7
87
0
Order By: Relevance
“…However, when the food item is liquid or aqueous, highly soluble polymeric films are undesirable [51] . The percentage solubility of the nanocomposites developed in the present study varied between 25.30 (FB10) and 32.16 (FM15), and may thus be considered as low-solubility films [52] . This indicates that they can be used to package a wide variety of food items, provided that their overall performance satisfies relevant legislation.…”
Section: Characterization Of Nanobiocompositesmentioning
confidence: 83%
“…However, when the food item is liquid or aqueous, highly soluble polymeric films are undesirable [51] . The percentage solubility of the nanocomposites developed in the present study varied between 25.30 (FB10) and 32.16 (FM15), and may thus be considered as low-solubility films [52] . This indicates that they can be used to package a wide variety of food items, provided that their overall performance satisfies relevant legislation.…”
Section: Characterization Of Nanobiocompositesmentioning
confidence: 83%
“…We have previously demonstrated that incorporation of guar gum and pea starch resulted in biocomposite edible films with improved physical and optical properties . However, to the best of our knowledge, there is no specific study on the effect of blending guar gum on mechanical and barrier properties of pea starch edible films.…”
Section: Introductionmentioning
confidence: 98%
“…Owing to long polymeric chain, high molecular weight, and wide availability of guar gum, it is a potential alternative for the development of a renewable source‐based biodegradable packaging material as in comparison with other biopolymers . Very few reports exist on guar gum‐based biodegradable packaging films .…”
Section: Introductionmentioning
confidence: 99%
“…The solution was heated at 90 °C for 20 min upon constant stirring. The suspension was then cooled until room temperature with mild magnetic stirring . The film solution was prepared 1 day before use.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, it has been demonstrated that pea starch in combination with guar gum produced biocomposite edible films with desirable physical, optical, and mechanical characteristics . It was shown that pea starch and guar gum (PSGG) can be potential alternatives for production of renewable source‐based biodegradable edible coatings owing to their long polymeric chain, high molecular weight, and wide availability.…”
Section: Introductionmentioning
confidence: 99%